2011
DOI: 10.1152/ajplung.00048.2010
|View full text |Cite
|
Sign up to set email alerts
|

Lack of CCR7 induces pulmonary hypertension involving perivascular leukocyte infiltration and inflammation

Abstract: The chemokine receptor CCR7 regulates lymphocyte trafficking, and CCR7 deficiency induces infiltration of T and B cells adjacent to vessels in mouse lungs. Perivascular infiltration of T and B cells has also been found in human pulmonary arterial hypertension, and downregulation of the CCR7 receptor in circulating leukocytes of such patients has been observed. To investigate whether changes in the CCR7 system contribute to the pathogenesis of pulmonary hypertension, we utilized mice deficient of the CCR7 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…Ϫ/Ϫ , and ASC Ϫ/Ϫ mice exposed to 3 mo of hypoxia and their controls (n ϭ 6) were stained with the endothelial cell marker von Willebrand factor and smooth muscle ␣-actin as previously described (25). The total number of peripheral arteries at alveolar duct and wall level was counted as the number of arteries positive for von Willebrand factor per 100 alveoli.…”
Section: Methodsmentioning
confidence: 99%
“…Ϫ/Ϫ , and ASC Ϫ/Ϫ mice exposed to 3 mo of hypoxia and their controls (n ϭ 6) were stained with the endothelial cell marker von Willebrand factor and smooth muscle ␣-actin as previously described (25). The total number of peripheral arteries at alveolar duct and wall level was counted as the number of arteries positive for von Willebrand factor per 100 alveoli.…”
Section: Methodsmentioning
confidence: 99%
“…Although mem IgD was not found in blood IgT + B cells (21), it might be possible that mem IgD is found in IgT + cells from mucosal tissues. In mammalian lungs, CCR7 regulates normal pulmonary leukocyte homeostasis because the lack of CCR7 induces pulmonary hypertension involving perivascular infiltration of B and T lymphocytes (42). The reason for this is that CCR7 not only efficiently infiltrates leukocytes to extralymphoid tissues and sites of inflammation but also mediates the exit of leukocytes from these tissues through afferent lymph vessels (43), although again, most of these studies were focused on T cells (44).…”
Section: Effect Of Vhsv Infection On the Distribution Of Ccr7 + Cellsmentioning
confidence: 99%
“…1 DC are absent to suppress lymphocytes by anergy (6). Recently, it was demonstrated that pulmonary lymphoid neogenesis accompanies idiopathic PH (7).…”
mentioning
confidence: 99%